New insights on the age for neutering dogs - Saraiva, Ana de Fátima Barradas (2019)
The current report was carried out for the completion of the Master’s degree in veterinary Medicine and is divided into two parts. The first part is formed by a description of the cases followed during the four-month traineeship completed at Priory Veterinary Surgeons. The most prevalent medical field was dermatology, with a relative frequency of 26% (n= 474), followed by gastroenterology representing 18% of total cases. The second part is composed of a review of the current literature on the proposed benefits and detriments of gonadectomy in dogs and whether performing it at a specific age causes or prevents specific health issues; RESUMO: O presente relatório foi realizado no âmbito do Mestrado Integrado em Medicina Veterinária e está dividido em duas partes. A primeira parte é constituída por uma descrição da casuística observada durante o estágio curricular de quatro meses realizado no Priory Veterinary Surgeons. A área mais prevalente foi dermatologia, com uma frequência relativa de 27% (n=480), seguida da gastroenterologia, que representou 18% dos casos totais. Na segunda parte é realizada uma revisão da literatura atual sobre os benefícios e malefícios inerentes à gonadectomia em cães e se a sua realização em determinada idade específica causa ou impede problemas de saúde específicos